Fused pentacyclic electron acceptors with four cis-arranged alkyl side chains for efficient polymer solar cells. Issue 8 (8th February 2018) - Hou, Ran; Li, Miao; Feng, Shiyu; Liu, Yahui; Wu, Liangliang; Bi, Zhaozhao; Xu, Xinjun; Ma, Wei; Bo, Zhishan
Abstract : A fused pentacyclic small molecule acceptor with cis -arranged alkyl side chains was firstly synthesized and applied in polymer solar cells. Abstract : We have synthesized a novel kind of fused pentacyclic small molecule acceptor (IDIDT-C8 ) with cis -arranged alkyl side chains for the first time. Specifically, four aliphatic groups were introduced on one side of the diindeno[1, 2- b :2′, 1′- d ]thiophene unit to construct the molecular backbone with cis -arranged side chains. Such cis -arranged alkyl side chains can play a significant role in adjusting the crystallinity and molecular packing styles. Therefore, the formation of large molecular aggregations can be suppressed in the photoactive layer. Accordingly, polymer solar cells (PSCs) fabricated with polymer PBDB-T as a donor andIDIDT-C8 as an acceptor show a maximum power conversion efficiency of 10.10% with an FF of 65.9%, a J sc of 15.81 mA cm −2, and a high V oc of 0.97 V, which are among the highest values for single-junction PSCs with fused five-ring electron acceptors up to now.